2012
DOI: 10.1186/1471-2407-12-120
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for triple-negative breast cancer tumor-initiating cells (TNBC-TICs) exhibits similar aggressive phenotype to the human disease

Abstract: BackgroundTriple-negative breast cancer (TNBC) exhibit characteristics quite distinct from other kinds of breast cancer, presenting as an aggressive disease--recurring and metastasizing more often than other kinds of breast cancer, without tumor-specific treatment options and accounts for 15% of all types of breast cancer with higher percentages in premenopausal African-American and Hispanic women. The reason for this aggressive phenotype is currently the focus of intensive research. However, progress is hampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 44 publications
7
139
1
2
Order By: Relevance
“…In this report, we present the effect of brazilein on several physiological targets on cancer development, especially on metastatic breast cancer cells. We used 4T1 cells line that has been recognized as active cells in proliferation and migration (Kaur et al, 2012). Comprehensively, we found that brazilein exhibited middle or low cytotoxic effect, cell cycle modulation, apoptosis induction, and inhibition of cells migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we present the effect of brazilein on several physiological targets on cancer development, especially on metastatic breast cancer cells. We used 4T1 cells line that has been recognized as active cells in proliferation and migration (Kaur et al, 2012). Comprehensively, we found that brazilein exhibited middle or low cytotoxic effect, cell cycle modulation, apoptosis induction, and inhibition of cells migration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cancer progression usually involve aberration of cell proliferation and cell migration as well as invasion (Kemper et al, 2014). The 4T1 cell is the example of metastatic breast cancer that *Corresponding author: Riris Istighfari Jenie Faculty of Pharmacy, Universitas Gadjah Mada, Indonesia, 55281 Email: riris_jenie@ugm.ac.id (Laksmiani et al, 2015) performs active proliferation, migration and invasion (Kaur et al, 2012). Some growth signaling involve in the 4T1 cells proliferation including activation of NFκB transcription factor (Tsubaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that, these cells have a considerable subpopulation of CSC that confer proven IR resistance [92,101,[107][108][109][110][111]. These characteristics make these cells a reliable candidate to compare their IR biological response to that of aMSCs.…”
Section: Mesenchymal Stromal/stem Cells Therapymentioning
confidence: 99%
“…We know that spontaneous metastasis usually occurs in late stages of cancer, and 4T1, a representative of metastasis, primarily metastasizes to the lung. 11 Likewise, ex vivo imaging ( Figure 8C) revealed that bioluminescence signal could be detected in the lung (yellow arrow) of control group, which revealed that many tumor cells were most likely to metastasize to lungs. In order to confirm this, we dissected lung tissues from mice and fixed them with Bouin's solution to observe tumor metastasis to lungs.…”
Section: Inhibition Of Spontaneous Metastasis and Postoperative Metasmentioning
confidence: 99%
“…The 4T1 mouse mammary tumor cell line is one of only a few breast cancer models having the capacity to metastasize efficiently to sites similar to human breast cancer when implanted orthotopically, and it is also a late stage breast cancer. 11,12 So, 4T1 cells were selected as the model system in the present study. Considering that there is no commercialized product of Lx2-32c, we employed Cremophor EL and ethanol (v/v =1:1) as the solvent to obtain Lx2-32c solution, referred to as Taxol ® , in this study.…”
Section: Introductionmentioning
confidence: 99%